Main challenges of closed/abandoned coal mine resource utilization in China. Issue 22 (16th November 2020) - Lu, Ping; Zhou, Lai; Cheng, Sen; Zhu, Xueqiang; Yuan, Tao; Chen, Di; Feng, Qiyan
ABSTRACT: China launches large-scale coal mines closure plan. This paper discusses the utilization of underground space and the redevelopment of energy resources after mine closure and points out main challenges. Suggestions are made: Chinese government needs to make the top-level planning, design, and guidance to balance economic, social, and environmental interest. Researchers and engineers need to investigate the underground available space characteristics and guarantee the underground space safety; deal with mechanism, basic theories, and key technologies for domestic unconventional natural gas development and utilization; develop a mature underground gasification development and utilization technology system; reveal the groundwater contamination mechanism and improve the water resource quality; and pay attention to microbial community shifts in response to pollution during the process of closed/abandoned coal mines restoration.